Reverse logistics network design under greenness, reliability and refurbished product demand considerations. (2017) - Venkatadri, Uday; Diallo, Claver; Ghayebloo, Sima
The aim of this paper is to present a new closed-loop supply chain (CLSC) network design model for multi-component and multi-product systems. This integrated model is more representative of industrial operations and takes into account the following important design factors: multi-component products, design for disassembly, existence of a secondary market for refurbished products, bill of material for product decomposition into parts, reliability and greenness levels of parts/products. A mixed-integer programming model is developed for a forward/reverse logistic network that includes suppliers, customer zones, inspection, repair and disassembly centres (IRDC), and a recycling centre. A wide range of numerical experiments are conducted and sensitivity analyses are carried out on various parameters yielding valuable managerial insights. The model is used to expose the effects of parts reliability and product greenness on the reverse flow and the economical operating market range for refurbished products in the reverse flow.